VULVAR SURGERY AND SEXUALITY - Py Gomes da Silveira, Gustavo (2005)
The vulve, an externe organ of sexual function, need special cares when it's necessary a surgical intervention. The great variety of size and of structural vulve constitution makes that some people interpret as an anomalie this anatomic variancy absolutely normal (like small lips a little bit larger than the average. Then, the plastic of small lips it's a surgery that exists but only in excepcional indications. The surgeries of cysts and benigne tumors should be delicated, for not keep sequel. The vulvar cancer, that becoming more frequent in young adults, had, as a primary preferential treatment, the radical vulvectomy with lymphadenectomy, used today just in advanced tumors. With patient younger and younger, tumors more and more less advanced, on top of all that the fashion of conservative surgeries for cancer, to carry out the adoption of conservative treatment. Today the treatment for invasive vulvar cancer has as an official pattern, in lateral tumors, a surgery that keeps the clitoris and the against side hemivulve, with positive repercussion about sexuality.